Spongy solid amine CO2 adsorption material and preparation method thereof
By introducing temperature -sensitive monomers on polyethylene amine matrix and preparing high -phase emulsion template method, the existing solid amine materials have insufficient adsorption capacity during the adsorption and regeneration of CO2 The problem has achieved efficient and low -energy CO2 adsorption and regeneration effects.
Patent Information
- Application Number
- CN202411498601.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
During the CO2 adsorption and regeneration process, existing solid amine materials have problems such as insufficient adsorption capacity, high desorption temperature, large regeneration energy consumption, and easy formation of irreversible urea and its derivatives by adsorbents.
Polyethylene amine is used as a substrate, a temperature -sensitive monomer is introduced through the Michael bonus reaction, and the cross -linked preparation is formed under high -end phase emulsion templates to form a sponge -like solid amine CO2 adsorption material.
The CO2 adsorption capacity and adsorption dynamic performance of the adsorption material are improved, and the aid temperature and renewable energy consumption are reduced, and the material has stable and efficient adsorption performance.
Smart Images

Figure CN119368153A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a sponge-like solid amine CO2 adsorption material and a preparation method thereof. Background Art
[0002] With the acceleration of the global industrialization process, global warming and the resulting climate change caused by huge CO2 emissions have become key issues that humans urgently need to solve. Clean energy such as wind energy, hydropower, solar energy and hydrogen energy can completely replace fossil energy in the short term. The application of high-performance CO2 adsorption materials is an effective means to solve climate problems. Ideal CO2 adsorption materials should have the characteristics of high CO2 adsorption capacity, fast adsorption kinetics, high selectivity, low preparation and operation costs. The adsorption capacity, adsorption kinetics and selectivity are related to the structure of the material and the number of effective adsorption sites, and the cost is related to the price of raw materials, the complexity of the preparation process and the regeneration performance of the material.
[0003] Most existing solid amine materials are supported. First, a porous carrier is synthesized, and then the organic amine is loaded into the carrier by physical impregnation or other methods. On the one hand, the loading of amines in the carrier will inevitably lead to pore blockage, and the carrier pore structure needs to be designed and optimized. On the other hand, there is basically no interaction between the polymer carrier and the amine, and the loading of amines has a theoretical limit, and it is easy to lose in multiple cycles. At the same time, the adsorbent often needs to be desorbed at above 90°C, which has high energy consumption and is easy to cause the adsorbent to combine with CO2 to form urea and its derivatives, resulting in an irreversible decrease in adsorption capacity.
[0004] In order to increase the adsorption capacity, people began to try to prepare solid amine adsorbents based on amines. In the literature with Doi 10.1039 / c6gc01416j, an amine-terminated hyperbranched polymer HBP-NH2 was synthesized by Michael addition reaction of organic small molecule amines and methyl acrylate, and then a CO2-imprinted solid amine adsorbent with high amine density was prepared by pre-adsorbing CO2 and cross-linking with glutaraldehyde, with an adsorption capacity of up to 7.65mmol / g. In the literature with Doi 10.1021 / acs.langmuir.9b03694, microspheres based on polyethyleneimine were prepared by W / O emulsion, which had good adsorption kinetics and high CO2 adsorption capacity. The CO2 adsorption capacity was 7.28mmol / g at 20℃ and 0.1bar.
[0005] In order to lower the desorption temperature and thus reduce the regeneration energy consumption and cost, people modify the amine group or carrier to give it temperature-responsive properties. In the literature with Doi 10.1021 / acs.langmuir.8b02493, propylene oxide was further introduced into the terminal amino hyperbranched polymer for modification. Although the adsorption capacity was slightly reduced, the material could be completely regenerated at 85°C. In the literature with Doi 10.1016 / j.jenvman.2021.112722, acrylamide and N-isopropylacrylamide were copolymerized and grafted onto sisal fibers. The introduction of N-isopropylacrylamide gave the material significant temperature-sensitive properties, and the water absorption and swelling rate of the material at different temperatures changed significantly. By controlling the copolymer monomer ratio, the CO2 adsorption capacity of the adsorbent did not decrease significantly, but the desorption temperature could be reduced to 60°C. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a sponge-like solid amine CO2 adsorption material and a preparation method thereof.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a sponge-like solid amine CO2 adsorption material, which takes polyethyleneimine as a matrix, first introduces a thermosensitive monomer through Michael addition, and then crosslinks and solidifies with a crosslinking agent in the presence of a high internal phase emulsion template to obtain a sponge-like solid amine CO2 adsorption material.
[0009] In certain specific embodiments, the method for preparing the sponge-like solid amine CO2 adsorbent material specifically comprises the following steps:
[0010] (1) adding polyethyleneimine and a thermosensitive monomer into water, mixing them evenly and performing a Michael addition reaction to obtain a polyethyleneimine aqueous solution modified with a thermosensitive monomer;
[0011] (2) adding a surfactant to the polyethyleneimine aqueous solution obtained in step (1) as the water phase and stirring evenly; weighing toluene and adding a crosslinking agent thereto as the oil phase; dropping the oil phase into the water phase while stirring, mixing evenly, to obtain a high internal phase emulsion;
[0012] (3) transferring the high internal phase emulsion prepared in step (2) to a polytetrafluoroethylene mold for cross-linking and curing, and washing and drying after the reaction to obtain a sponge-like solid amine CO2 adsorption material.
[0013] In some specific embodiments, the temperature-sensitive monomer is an alkylamide substance, the cross-linking agent is a glycidyl ether substance, and the surfactant is Triton X-405.
[0014] Among them, alkylamides are preferred as the providers of thermosensitive groups, mainly because alkylamides have a lower critical solution temperature (LCST). When the ambient temperature is lower than the LCST, the polar groups (such as amide groups) in the alkylamides form intermolecular hydrogen bonds with water molecules, and the polymer molecules are stretched and stretched, showing hydrophilic properties; when the ambient temperature is higher than the LCST, the intermolecular hydrogen bonds are destroyed, and the amide groups will cooperate to form intramolecular hydrogen bonds with each other, so that the polymer presents a helical shape to expel water molecules, showing hydrophobic properties.
[0015] Furthermore, the alkylamide substance is one of N-isopropylacrylamide, isobutyryl chloride, and isobutyric anhydride; the cross-linking agent is one of ethylene glycol diglycidyl ether, glycerol triglycidyl ether, butanediol diglycidyl ether, hexanediol diglycidyl ether, and resorcinol diglycidyl ether.
[0016] N-isopropylacrylamide is further preferred because it has a lower LCST of about 38°C, good reaction activity and is easy to modify. After being combined with polyethyleneimine, it can reduce the CO2 desorption temperature of the adsorbent.
[0017] In some specific embodiments, the molecular weight of the polyethyleneimine is 600-70000; when the molecular weight of the polyethyleneimine is small, the viscosity of the obtained emulsion system is low and unstable, and the amount of cross-linking agent required for cross-linking molding is also large; the cross-linking agent does not contain active adsorption sites, so the less the amount of cross-linking agent is, the higher the adsorption amount per unit mass of the obtained adsorbent; therefore, polyethyleneimine raw materials with large molecular weight are preferred without affecting the stability of the emulsion.
[0018] In certain specific embodiments, when the molecular weight of the polyethyleneimine used is relatively large, the polyethyleneimine is configured into an aqueous solution with a mass concentration of 5wt%-15wt%. When the concentration of the polyethyleneimine aqueous solution is relatively low, the distance between adjacent polyethyleneimine molecules is relatively far, resulting in that some polyethyleneimine cannot be completely cross-linked; when the concentration of the polyethyleneimine aqueous solution is relatively high, the interpenetrating network structure formed will become thicker and cover each other, which is not conducive to the diffusion and adsorption of CO2.
[0019] In certain specific embodiments, the mass ratio of polyethyleneimine to the temperature-sensitive monomer in step (1) is 1:(0.1-1). The more the temperature-sensitive monomer is added, the more obvious the temperature-sensitive property of the obtained material is, and the lower the desorption temperature is; but since alkylamide substances do not provide active adsorption sites, the more the alkylamide substances are added, the lower the adsorption capacity of the obtained material is. Therefore, it is necessary to comprehensively consider the adsorption capacity and the desorption temperature to determine the optimal amount of alkylamide substances added.
[0020] In certain specific embodiments, the volume ratio of the polyethyleneimine aqueous solution to toluene is 1:(2.85-5); the mass ratio of the polyethyleneimine to Triton X-405 is 1:(2.7-2.9). When the volume ratio of the polyethyleneimine aqueous solution to toluene is greater than 1:2.85, the resulting material will not have an interconnected through-hole structure. The smaller the water-to-oil ratio, the larger the through-hole size of the resulting material, the smaller the material density, but the more unstable the emulsion. Therefore, it is necessary to reduce the water-to-oil ratio while ensuring the stability of the emulsion.
[0021] In certain specific embodiments, the reaction temperature of the Michael addition reaction is 50-80° C., and the reaction time is 60-75 hours.
[0022] In some specific embodiments, the mass ratio of the polyethyleneimine to the cross-linking agent in the reaction system of the sponge-like solid amine CO2 adsorbent material is 1: (0.125-1)
[0023] In some specific embodiments, the reaction temperature of the cross-linking reaction is 50-70° C., and the reaction time is 4-8 hours.
[0024] In some specific embodiments, in step (2), the mixing is carried out by stirring, the stirring speed is 500-1200 rpm, and the stirring time is 10-60 minutes.
[0025] In certain specific embodiments, the solvent used for washing in step (3) is anhydrous ethanol, and the method used is Soxhlet extraction.
[0026] In certain specific embodiments, the drying in step (3) is performed by vacuum drying at a drying temperature of 60°C.
[0027] A sponge-like solid amine CO2 adsorption material prepared according to the above-mentioned preparation method, wherein the sponge-like solid amine CO2 adsorption material has through pores of μm to mm level and a water absorption swelling rate of 250-900%.
[0028] Compared with the prior art, the present invention has at least the following advantages:
[0029] (1) The preparation method provided by the present invention, first, the adsorbent material is based on polyethyleneimine, which has a large number of effective CO2 adsorption sites, so that the number of active adsorption sites per unit mass of the adsorbent material is large, thereby improving the CO2 adsorption capacity of the adsorbent material; secondly, the polyethyleneimine is thermosensitively modified by Michael addition, so that the synthesized material can be desorbed and regenerated at a lower temperature, thereby reducing the regeneration energy consumption; thirdly, by adopting a high internal phase emulsion template method for synthesis, the adsorbent material has a typical interconnected through-pore structure of μm to mm level, which is beneficial to the mass transfer and diffusion of gas molecules inside the adsorbent, further improving the adsorption capacity and adsorption kinetics of the adsorbent; the water absorption swelling rate of the adsorbent material obtained by the preparation method is 250-900%, and the presence of water molecules can promote the mass transfer and diffusion of gas molecules inside the adsorbent, thereby achieving efficient CO2 adsorption under humid conditions.
[0030] (2) The sponge-like solid amine CO2 adsorption material provided by the present invention is based on polyethyleneimine, has a higher amine group density than traditional supported solid amine CO2 adsorption materials, and has a higher CO2 adsorption capacity.
[0031] (3) The present invention uses a high internal phase emulsion template to prepare a sponge-like solid amine CO2 adsorbent material with a through-pore structure of μm to mm level, which is beneficial to the mass transfer and diffusion of CO2 gas inside the adsorbent material, promotes the adsorption kinetics of the adsorbent material, and further improves the CO2 adsorption capacity and amine-based efficiency.
[0032] (4) The present invention introduces a temperature-sensitive group into polyethyleneimine, and the prepared adsorbent material has both high CO2 adsorption capacity and low desorption temperature, thereby reducing the regeneration energy consumption of the adsorbent material.
[0033] (5) The high internal phase emulsion template method and Michael addition method provided by the present invention are used to prepare sponge-like solid amine CO2 adsorption materials. The preparation method is simple, the conditions are mild, and the reaction scale is easy to expand, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0035] Figure 1 This is a SEM image of the solid amine CO2 adsorbent material prepared in Example 1 of the present invention, wherein Figure 1 a is the SEM image of the solid amine CO2 adsorption material at 100 μm; Figure 1 b is the SEM image of the solid amine CO2 adsorption material at 20 μm;
[0036] Figure 2This is a SEM image (50 μm) of the solid amine CO2 adsorbent material prepared in Example 2 of the present invention;
[0037] Figure 3 The infrared spectrum (a) and the carbon nuclear magnetic resonance spectrum (b) of the solid amine CO2 adsorption material prepared in Example 2 of the present invention;
[0038] Figure 4 This is a SEM image of the adsorption material prepared in Comparative Examples 1-4 of the present invention;
[0039] Figure 5 The adsorption breakthrough curves of the adsorbent materials prepared in Test Example 2, Comparative Example 2 and Comparative Example 3 of the present invention;
[0040] Figure 6 The water absorption swelling rate test results of the adsorbent materials prepared in Examples 2, 4 and 3 of the present invention;
[0041] Figure 7 The regeneration performance test results of the adsorbent materials prepared in Example 2, Example 3 and Experimental Examples 8 and 9 in Example 4 of the present invention at different temperatures are shown. DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0043] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0044] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0045] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0046] In the following examples, polyethyleneimine was purchased from Shanghai MacLean Co., Ltd., and except for Mw=70000 which is a 50wt% aqueous solution, the purity of the other products is 99%; ethylene glycol diglycidyl ether was purchased from TCI Co., Ltd.; anhydrous ethanol and toluene were purchased from Guangzhou Chemical Reagent Factory with a purity of AR; Triton X-405 was purchased from Yuanye Biotechnology Co., Ltd. with a purity of BR, 70%; N-isopropylacrylamide was purchased from Alfa Aesar Co., Ltd. with a purity of 99% (including stabilizer).
[0047] Example 1
[0048] This embodiment provides a method for preparing a sponge-like solid amine CO2 adsorbent material, which specifically comprises the following steps:
[0049] (1) Weigh 2 g of polyethyleneimine (Mw=10000) and dilute it to 10 wt% in deionized water to obtain a polyethyleneimine aqueous solution;
[0050] (2) adding 5.6 g of Triton X-405 as the aqueous phase to the polyethyleneimine aqueous solution prepared in step (1), and stirring at a speed of 500 rpm for 15 minutes; weighing 100 mL of toluene, and adding 1 g of ethylene glycol diglycidyl ether thereto as the oil phase; adding the oil phase dropwise to the aqueous phase described in step (1) at a speed of 500 rpm to obtain a milky white high internal phase emulsion;
[0051] (3) The high internal phase emulsion obtained in step (2) was transferred to a polytetrafluoroethylene mold and reacted at 60° C. for 4 hours. After the reaction, the obtained sponge-like material was Soxhlet extracted with anhydrous ethanol for 24 hours and vacuum dried at 60° C. to obtain a sponge-like solid amine CO2 adsorption material, which was labeled as PEI10K-2-EGDE-HIPE.
[0052] The number after PEI represents the weight average molecular weight of polyethyleneimine, EGDE indicates that the crosslinking agent used is ethylene glycol diglycidyl ether, the value between PEI and EGDE represents the mass ratio of polyethyleneimine to ethylene glycol diglycidyl ether, and HIPE indicates the high internal phase emulsion template used;
[0053] The solid amine CO2 adsorbent material prepared in this embodiment is subjected to electron microscope scanning, and its SEM image is as follows: Figure 1 As shown, from Figure 1 It can be seen that the adsorption material prepared in Example 1 has a sponge-like structure with three-dimensional interconnected pores.
[0054] Example 2
[0055] This embodiment provides a method for preparing a sponge-like solid amine CO2 adsorbent material, which specifically comprises the following steps:
[0056] (1) Weigh 4 g of polyethyleneimine (50 wt % aqueous solution, Mw=70000) and dilute it to 10 wt % in deionized water, add 0.4 g of N-isopropylacrylamide, mix well with a stirrer, and react at 60° C. for 72 hours to obtain a polyethyleneimine aqueous solution modified with a thermosensitive monomer.
[0057] (2) adding 5.6 g of Triton X-405 as the aqueous phase to the polyethyleneimine aqueous solution obtained in step (1), and stirring at a rotation speed of 500 rpm for 15 minutes; weighing 100 mL of toluene, and adding 0.25 g of ethylene glycol diglycidyl ether thereto as the oil phase; adding the oil phase dropwise to the aqueous phase at a rotation speed of 500 rpm to obtain a light yellow high internal phase emulsion;
[0058] (3) The high internal phase emulsion obtained in step (2) is transferred to a polytetrafluoroethylene mold and reacted at 60° C. for 4 hours. After the reaction, the obtained sponge-like material is extracted with anhydrous ethanol for 24 hours and vacuum dried at 60° C. to obtain a sponge-like solid amine CO2 adsorption material with temperature sensitivity, which is marked as 0.2NIPAM-PEI70K-HIPE (wherein the number before NIPAM represents the mass ratio of N-isopropylacrylamide to polyethyleneimine).
[0059] The present application performs electron microscope scanning on the sponge-like solid amine CO2 adsorbent material prepared in this embodiment, and the SEM image thereof is as follows: Figure 2 As shown, from Figure 2 It can be seen that the adsorption material prepared in Example 2 retains a three-dimensional interconnected pore structure.
[0060] At the same time, the prepared sponge-like solid amine CO2 adsorbent material was identified and analyzed, and its infrared spectrum and nuclear magnetic resonance carbon spectrum were as follows: Figure 3 As shown, from Figure 3 As can be seen in the infrared spectrum of NIPAM (N-isopropylacrylamide), the amide I peak and amide II peak are located at 1657 cm -1 and 1546cm -1 After modification with N-isopropylacrylamide, the intensities of amide I and II peaks of 0.2NIPAM-PEI70K-HIPE were enhanced, indicating the successful introduction of NIPAM. -1 The -C=C- stretching vibration peak at 131ppm and 127ppm disappeared, indicating that NIPAM was introduced into the polyethyleneimine chain segment through Michael addition reaction. In the carbon NMR spectrum, the -C=C- characteristic peaks at 131ppm and 127ppm of 0.2NIPAM-PEI70K-HIPE disappeared, and two new characteristic peaks at 170ppm and 22ppm representing -C=O and -CH3 were added.
[0061] Example 3
[0062] This embodiment provides a method for preparing a sponge-like solid amine CO2 adsorbent material, which is basically the same as that of Example 2, except that the feed mass ratio of ethylene glycol diglycidyl ether to polyethyleneimine is different, as shown in Table 1:
[0063] Table 1 Mass ratio of different polyethyleneimine and ethylene glycol diglycidyl ether
[0064] Test Example 1 Test Example 2 Test Example 3 Test Example 4 Test Example 5 PEI:EGDE 16 8 4 2 1 EGDE(g) 0.125 0.25 0.5 1 2
[0065] Example 4
[0066] This embodiment provides a method for preparing a sponge-like solid amine CO2 adsorbent material, which is basically the same as that of Example 2, except that the feed mass ratio of polyethyleneimine to N-isopropylacrylamide is different, as shown in Table 2:
[0067] Table 2 Different mass ratios of N-isopropylacrylamide and polyethyleneimine
[0068] Test Example 6 Test Example 7 Test Example 8 Test Example 9 NIPAM:PEI 0.02 0.04 0.1 0.5 NIPAM(g) 0.04 0.08 0.2 1
[0069] Comparative Example 1
[0070] The preparation method of the sponge-like solid amine CO2 adsorption material provided in this comparative example is basically the same as that in Example 1, except that the mass of EGDE added is 0.25 g, and the mass ratio of EGDE to PEI is 1:8.
[0071] The solid amine CO2 adsorbent prepared in this comparative example was subjected to electron microscope scanning, and its SEM image is as follows: Figure 4 As shown in a, from Figure 4 It can be seen from a that the adsorption material prepared in Comparative Example 1 also has a three-dimensional interconnected pore structure.
[0072] Comparative Example 2
[0073] The preparation method of the adsorbent material provided in this comparative example comprises the following steps:
[0074] Weigh 4 g of polyethyleneimine (50 wt % aqueous solution, Mw = 70000) and dilute it to 10 wt % in deionized water, add 0.25 g of ethylene glycol diglycidyl ether, transfer the resulting solution to a polytetrafluoroethylene mold and react at 60° C. for 4 hours. After the reaction, the resulting gel block material is Soxhlet extracted with anhydrous ethanol for 24 hours and vacuum dried at 60° C. to obtain a gel block solid amine CO2 adsorption material, marked as PEI70K-8-EGDE-GEL, wherein the number after PEI represents the weight average molecular weight of polyethyleneimine, EGDE indicates that the cross-linking agent used is ethylene glycol diglycidyl ether, the value between PEI and EGDE represents the mass ratio of polyethyleneimine to ethylene glycol diglycidyl ether, and GEL represents the gel block morphology of the material.
[0075] The present application conducted electron microscope scanning on the adsorption material prepared in this comparative example, and its SEM image is as follows Figure 4 As shown in b, from Figure 4 As can be seen in b, the adsorption material prepared in Comparative Example 2 has a dense gel block structure.
[0076] Comparative Example 3
[0077] The preparation method of the adsorbent material provided in this comparative example comprises the following steps:
[0078] (1) Weigh 6 g of polyethyleneimine (50 wt % aqueous solution, Mw=70000) and dilute it to 15 wt % in deionized water to obtain a polyethyleneimine aqueous solution;
[0079] (2) adding 5.6 g of Triton X-405 as the aqueous phase to the polyethyleneimine aqueous solution prepared in step (1), and stirring at a speed of 500 rpm for 15 minutes; weighing 100 mL of toluene, and adding 0.25 g of ethylene glycol diglycidyl ether thereto as the oil phase; adding the oil phase dropwise to the aqueous phase at a speed of 500 rpm to obtain a milky white high internal phase emulsion;
[0080] (3) The high internal phase emulsion was transferred to a polytetrafluoroethylene mold and reacted at 60° C. for 4 hours. After the reaction, the obtained sponge-like material was Soxhlet extracted with anhydrous ethanol for 24 hours and vacuum dried at 60° C. to obtain a sponge-like solid amine CO2 adsorption material.
[0081] The present application conducted electron microscope scanning on the adsorption material prepared in this comparative example, and its SEM image is as follows Figure 4 As shown in c, from Figure 4 As can be seen in c, the adsorption material prepared in Comparative Example 3 has a dense gel block structure.
[0082] Comparative Example 4
[0083] The preparation method of the adsorbent material provided in this comparative example comprises the following steps:
[0084] The preparation method of the sponge-like solid amine CO2 adsorption material provided in this comparative example is basically the same as that of Example 2, except that the mass of NIPAM added is 2 g, and the mass ratio of NIPAM to PEI is 1:1.
[0085] The solid amine CO2 adsorbent prepared in this comparative example was subjected to electron microscope scanning, and its SEM image is as follows: Figure 4 d, from Figure 4 As can be seen in Figure d, the adsorption material prepared in Comparative Example 1 maintains the original three-dimensional pore structure, but due to excessive addition of NIPAM, the three-dimensional pore structure shrinks to a certain extent.
[0086] Performance Test:
[0087] 1) Adsorption capacity test
[0088] The present application tests the adsorption capacity of the adsorption materials prepared in Example 1, Example 3 and Comparative Examples 2-3, specifically:
[0089] The adsorption amount is determined by the fixed bed method. A certain concentration of CO2 is passed through a fixed bed filled with a fully moistened sample. The CO2 concentration at the outlet is continuously measured by gas chromatography to obtain the CO2 adsorption breakthrough curve, which is calculated by formula 1:
[0090]
[0091] Wherein, Q is the equilibrium adsorption capacity of the material (mmol / g), t is the adsorption time (min), Cin is the inlet concentration of the adsorbed gas (vol%), Ceff is the outlet concentration of the adsorbed gas (vol%), V is the flow rate of the mixed gas (mL / min), and W is the mass of the adsorbent material (g). The results of the measurement are shown in Table 3, wherein the adsorption breakthrough curves of Test Example 2, Comparative Example 2 and Comparative Example 3 are shown in Table 3. Figure 5 As shown:
[0092] Table 3 Adsorption amount of adsorbent materials prepared in Example 1, Example 3 and Comparative Examples 1-3
[0093] Example 1 Test Example 2 Test Example 3 Test Example 4 Test Example 5 Comparative Example 2 Comparative Example 3 Adsorption 7.54 14.22 10.41 7.78 4.88 4.39 7.48
[0094] It can be seen from the data in Table 3 that the sponge-like solid amine CO2 adsorbent material prepared by the present invention has a high adsorption capacity. By comparing Example 1 and Test Example 4, it can be seen that the molecular weight of polyethyleneimine has little effect on the adsorption capacity of the adsorbent material, but during the test, the polyethyleneimine solution system with a larger molecular weight has a higher viscosity, and the obtained emulsion system is more stable.
[0095] It can be seen from comparative test examples 2-5 that the amount of ethylene glycol diglycidyl ether added has an important influence on the adsorption amount of the adsorbent material. The more ethylene glycol diglycidyl ether is added, the lower the adsorption amount of the prepared adsorbent material. However, the amount of ethylene glycol diglycidyl ether added cannot be too small. If it is too small, the emulsion system cannot be cross-linked and cured (such as test example 1).
[0096] By comparing Example 2 and Comparative Example 2, it can be seen that the adsorbent material prepared by the high internal phase emulsion template method of Example 2 has a typical three-dimensional interconnected pore structure, which is conducive to the mass transfer and diffusion of gas molecules inside the adsorbent material, and the adsorption sites inside the material are also easily exposed, so it has a faster adsorption speed and adsorption amount. The adsorbent material synthesized by the direct solution method of Comparative Example 2 has a typical gel block structure, and the diffusion of gas molecules inside the adsorbent material takes longer. Figure 5 The adsorption breakthrough curve shows a typical "long tail effect".
[0097] By comparing Test Example 2 and Comparative Example 3, it can be seen that when the concentration of the polyethyleneimine aqueous solution is high, the final cross-linking density of the adsorption material is high, and the polyethyleneimine layer is thicker, resulting in the mutual coverage of the formed interconnected pore structures, which is not conducive to the diffusion and adsorption of the gas, the adsorption rate of the material becomes slower, and the adsorption amount is reduced.
[0098] 2) Water absorption and swelling rate test
[0099] The present application also tests the water absorption swelling rate of the adsorbent material at different temperatures. The swelling rate is calculated by formula 2:
[0100] SR=(m s -m0) / m0 Formula 2
[0101] The water absorption swelling rate test was conducted on the adsorbent material 0.2NIPAM-PEI70K-HIPE prepared in Example 2, 1NIPAM-PEI70K-HIPE and 0.5NIPAM-PEI70K-HIPE prepared by adding different N-isopropylacrylamide contents in Example 4, and the adsorbent material PEI70K-8-EGDE-HIPE prepared without adding NIPAM in Example 3. The results are as follows: Figure 6 As shown, the water absorption swelling rate of the adsorption material introduced with NIPAM is significantly reduced with the increase of temperature, and the higher the content of introduced NIPAM, the more obvious the temperature responsiveness.
[0102] 3) Regeneration performance test
[0103] The present application also tests the regeneration performance of the adsorbent materials prepared in Example 2, Test Example 2 in Example 3, and Test Examples 8 and 9 in Example 4 at different temperatures. Figure 7 It can be seen from ab that the initial adsorption amount of the adsorption material PEI70K-8-EGDE-HIPE without NIPAM thermosensitive functional monomer is 14.22 mmol / g, which can basically remain stable after multiple cycles at 90°C, while the adsorption amount decreases significantly after one adsorption-desorption cycle at 80°C. Figure 7 0.1NIPAM-PEI70K-HIPE with a small amount of NIPAM added to the cd can be basically stably regenerated at 80°C, but cannot be completely regenerated at 70°C. After adding more NIPAM monomers, 0.2NIPAM-PEI70K-HIPE can be completely regenerated at 70°C, but cannot be completely regenerated at 60°C; 0.5NIPAM-PEI70K-HIPE can be completely regenerated at 60°C. However, with the increase of NIPAM content, the adsorption amount of the adsorbent material gradually decreases, and the initial adsorption amount of 0.5NIPAM-PEI70K-HIPE is only 5.3mmol / g; in practical applications, it is necessary to find a suitable amount of NIPAM addition to balance the effects of desorption temperature and adsorption amount.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a sponge-like solid amine CO2 adsorbent material, characterized in that: The method uses polyethyleneimine as a matrix, firstly introduces a thermosensitive monomer through Michael addition, and then crosslinks and solidifies with a crosslinking agent in the presence of a high internal phase emulsion template to obtain a sponge-like solid amine CO2 adsorption material.
2. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 1, characterized in that: The steps include: (1) preparing a polyethyleneimine aqueous solution, adding a thermosensitive monomer, mixing evenly, and performing a Michael addition reaction to obtain a polyethyleneimine aqueous solution modified with a thermosensitive monomer; (2) adding a surfactant to the polyethyleneimine aqueous solution obtained in step (1) as the water phase and stirring evenly; weighing toluene and adding a crosslinking agent thereto as the oil phase; dropping the oil phase into the water phase while stirring, mixing evenly, to obtain a high internal phase emulsion; (3) transferring the high internal phase emulsion prepared in step (2) to a polytetrafluoroethylene mold for cross-linking and curing, and washing and drying after the reaction to obtain a sponge-like solid amine CO2 adsorption material.
3. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 1, characterized in that: The temperature-sensitive monomer is an alkylamide substance, and the cross-linking agent is a glycidyl ether substance.
4. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 3, characterized in that: The alkylamide substance is one of N-isopropylacrylamide, isobutyryl chloride and isobutyric anhydride; the crosslinking agent is one of ethylene glycol diglycidyl ether, glycerol triglycidyl ether, butanediol diglycidyl ether, hexanediol diglycidyl ether and resorcinol diglycidyl ether.
5. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 1, characterized in that: The mass ratio of polyethyleneimine to the temperature-sensitive monomer in step (1) is 1:(0.1-1).
6. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 1, characterized in that: The reaction temperature of the Michael addition reaction is 50-80° C., and the reaction time is 60-75 hours.
7. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 4, characterized in that: The mass ratio of the polyethyleneimine to the cross-linking agent in the reaction system of the sponge-like solid amine CO2 adsorption material is 1:(0.125-1).
8. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 4, characterized in that: The reaction temperature of the cross-linking reaction is 50-70° C., and the reaction time is 4-8 hours.
9. The method for preparing a sponge-like solid amine CO2 adsorbent material according to claim 4, characterized in that: In the step (2), the mixing is carried out by stirring at a speed of 500-1200 rpm and for a time of 10-60 minutes.
10. A sponge-like solid amine CO2 adsorbent material prepared according to any one of the preparation methods of claims 1 to 8, characterized in that: The sponge-like solid amine CO2 adsorption material has through pores in the range of μm to mm, and a water absorption swelling rate of 250-900%.
Citation Information
Cited By
Amine-ammonium type bifunctional material for integration of carbon dioxide capture and utilization and preparation method of amine-ammonium type bifunctional material
CN119978461A